Heaven's Door : Immigration Policy and the American Economy - Borjas, George J. (Book collections on Project MUSE., 1999)
The U.S. took in more than a million immigrants per year in the late 1990s, more than at any other time in history. For humanitarian and many other reasons, this may be good news. But as George Borjas shows in Heaven's Door, it's decidedly mixed news for the American economy--and positively bad news for the country's poorest citizens. Widely regarded as the country's leading immigration economist, Borjas presents the most comprehensive, accessible, and up-to-date account yet of the economic impact of recent immigration on America. He reveals that the benefits of immigration have been.